Impact of Climate Change on Production and Productivity: A Case Study of Maize Research and Development In Nepal - Nayava, Janak Lal; Gurung, Dil Bahadur (Journal of Agriculture and Environment, 2010)
The relation between climate and maize production in Nepal was studied for the period 1970/71-2007/08. Due to the topographical differences within north-south span of the country, Nepal has wide variety of climatic condition. About 70 to 90% of the rainfall occurs during summer monsoon (June to September) and the rest of the months are almost dry. Maize is cultivated from March to May depending on the rainfall distribution. Due to the availability of improved seeds, the maize yield has been steadily increasing after 1987/1988. The national area and yield of maize is estimated to be 870,166ha and 2159kg/ha respectively in 2007/08. The present rate of annual increase of temperature is 0.04°C in Nepal. Trends of temperature rise are not uniform throughout Nepal. An increase of annual temperature at Rampur during 1968-2008 was only 0.039°C. However, at Rampur during the maize growing seasons, March/April - May, the trend of annual maximum temperature had not been changed, but during the month of June and July, the trend of increase of maximum temperature was 0.03°C to 0.04°C /year. Key words: Climate-change; Global-warming; Hill; Mountain; Nepal; Tarai The Journal of AGRICULTURE AND ENVIRONMENT Vol. 11, 2010 Page: 59-69 Uploaded Date: 15 September, 2010